Expert decisison support system (EDSS) for doctor selection at emergency department using case based reasoning technique - Sue, Qi Jian (2014)
In real world, emergency always happen and it always needed an immediate action to solve it as patient's treatment duration is very crucial. Besides, there is no expert system to decide which doctor has to handle which emergency case based on expertise and resource allocation. In this project, "Expert Decision Support System" is to come out with The fast decision as it will be implemented to an emergency department and it needs a quick decision. The objective of this project is to design and develop an expert decision support system that able to decide which doctor to be assigned to which case based on type of emergency, prioritize which case should handle first based on stage of emergency. In this project, the proposed method that will be implemented is Case-Based Reasoning (CBR) technique in doctor selection process. By the end of this project, this system will be implemented in emergency department in order to come out with a support decision for doctor selection in each emergency case. This system is designed specifically for medical staff in emergency department.